In the company of killers : a novel - Christy, Bryan (G.P. Putnam's Sons, 2021)
"Tom Klay is a celebrated investigative wildlife reporter for the esteemed magazine, The Sovereign. But Klay is not just a journalist. His reporting is cover for an even more dangerous job: CIA agent. Klay's press credentials make him a perfect spy - able to travel the globe, engage both politicians and warlords, and openly record what he sees. While on assignment in Kenya, Klay is attacked and his closest friend is murdered. Soon Klay's carefully constructed double life unravels as his ambition turns to revenge. The CIA has an answer. Klay is offered a devil's bargain to capture the man who killed his friend by infiltrating the offices of the woman he once loved, South Africa's special prosecutor, Hungry Khoza. But Klay soon discovers that he and Hungry are part of a larger, more lethal game - one that involves a ruthless mercenary and a global superpower."--Publisher.